Understanding the Impact of Climate Change on Hydropower : The Case of Cameroon - Grijsen, Johan (World Bank, Washington, DC, 2014)
The Africa energy unit (AFTEG) of the World Bank has obtained financing from the trust fund for environmentally and socially sustainable development (TFESSD) funded by Finland and Norway for work towards understanding the impact of climate change on hydropower: the case of Cameroon. The development objective of this activity is: (i) to develop tools for assessing climate change impacts on the operation of hydraulic infrastructure such as regulating dams and hydropower plants in the Sanaga river basin, and (ii) to take steps towards an institutional framework for climate resilient water resources management in Cameroon. The aim of this initiative is to build resilience to climate risks into water management in general and hydropower development in Cameroon in particular. The study includes three components: (i) develop suitable climate change scenarios for the Sanaga basin, support the electricity development corporation (EDC) of Cameroon to develop a reliable hydrological model for the Sanaga river basin, and derive climate change impacts on the potential generation capacity in the Sanaga basin in the context of changing hydrology; (ii) assess the impact of climate change on the future operation of Lom Pangar dam and three other regulating dams in the Sanaga basin and support the establishment of an operational regime of hydraulic infrastructures in the Sanaga river basin, in a consultative manner with water users and taking into account equitable sharing of resources between users and environmental flows; and (iii) assess future impacts of climate change on water resources availability and management in Cameroon. This assessment also aims to provide an analytical base for increased dialogue on climate variability and change and on integrated management of water resources in Cameroon. The assessment will identify information and knowledge gaps and priorities for future studies and activities.